2008
DOI: 10.1007/s10620-008-0577-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rebamipide on Quality of Peptic Ulcer Healing in Rat

Abstract: The aim of this study is to elucidate the effects and the mechanism of rebamipide, omeprazole, and their combination treatment on quality of peptic ulcer healing (QOUH). Peptic ulcer models were induced by acetic acid exposure of the serosa of rat stomach. Forty Sprague-Dawley (SD) rats were divided randomly into four groups of ten rats each. Saline 2 ml/d (group 1), rebamipide 60 mg/kg/d (group 2), omeprazole 10 mg/kg/d (group 3) as well as its combination regimen (group 4) were administrated for 7 days. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
5
1
Order By: Relevance
“…19,20 A recent ani- mal study suggested that rebamipide might enhance the quality of ulcer healing by increasing levels of prostaglandin E 2 and decreasing levels of interleukin-8 and malondialdehyde. 21 Interestingly, in this study, the artificial ulcer healing rate was higher in the PPI and rebamipide combination group regardless of the initial ulcer size, whereas a previous smaller study suggested that this 4-week combination therapy was more effective than PPI alone for treating ulcers larger than 20 mm. 6 This discrepancy can be explained by the difference in the primary outcomes of each study.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…19,20 A recent ani- mal study suggested that rebamipide might enhance the quality of ulcer healing by increasing levels of prostaglandin E 2 and decreasing levels of interleukin-8 and malondialdehyde. 21 Interestingly, in this study, the artificial ulcer healing rate was higher in the PPI and rebamipide combination group regardless of the initial ulcer size, whereas a previous smaller study suggested that this 4-week combination therapy was more effective than PPI alone for treating ulcers larger than 20 mm. 6 This discrepancy can be explained by the difference in the primary outcomes of each study.…”
Section: Discussioncontrasting
confidence: 56%
“…11 Rebamipide not only can promote peptic ulcer healing but also can reduce its recurrence by improving quality of ulcer healing related to the inhibition of inflammatory responses. 11,21,29 In ESD-induced ulcers, it is unclear whether high quality of ulcer healing can reduce the recurrence of artificial ulcers. Although EMR-induced ulcers might heal faster, recur less often, or require shorter treatments than peptic ulcers, 3,30 further studies to investigate the effects of quality of ulcer healing in ESD-induced ulcers, which are usually larger and deeper than EMR-induced ulcers, should be conducted in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Increased PG synthesis was previously suggested as a possible mechanism for mucosal protection of rebamipide [ 16 , 17 ]. If so, rebamipide should not have a protective effect in NSAID-induced gastric damage through modulation of PG synthesis, since NSAIDs block the activity of cyclooxygenases.…”
Section: Discussionmentioning
confidence: 99%
“…Rebamipide has been described as a GI mucosal protector agent with promising results in prophylaxis and treatment of GI ulcers caused by NSAIDs, H. pylori or endoscopic submucosal dissection [ 9 – 15 ]. Results from animal studies have suggested that the protective effects of rebamipide are attributable to stimulation of prostaglandin (PG) synthesis [ 16 , 17 ]. In healthy volunteers, concomitant administration of rebamipide 100 mg with ibuprofen 600 mg t.i.d.…”
Section: Introductionmentioning
confidence: 99%
“…These actions increase the gastric mucosal blood flow at the ulcer margin, an important factor for ulcer healing, and accelerate the mucosal or submucosal reconstruction of damaged structures (24,26). A recent animal study suggested that treatment with rebamipide enhances the quality of ulcer healing by increasing the level of prostaglandin E2 and decreasing the levels of interleukin-8 and malondialdehyde (27). Previous studies have also reported that ulcer healing is associated with both the lesion size and tumor location.…”
Section: Discussionmentioning
confidence: 99%